Effects of ground configurations on the slipstream and near wake of a high-speed train. Issue 168 (September 2017) - Xia, Chao; Wang, Hanfeng; Shan, Xizhuang; Yang, Zhigang; Li, Qiliang
Abstract: The effects of ground configurations on the slipstream and near wake of a high-speed train are numerically investigated with improved delayed detached eddy simulation (IDDES). Both time-averaged and instantaneous near wake structures and the associated distribution of slipstream velocity are compared for two ground configurations, i.e., stationary ground (SG) and moving ground (MG) conditions. The ground configuration has pronounced effects on the tail vortex structures and the associated slipstream velocity distribution. For both ground configurations, the large scale longitudinal vortices in the near wake are always associated with high slipstream velocity. These tail vortices oscillate more violently for the SG case relative to the MG case. Thus, they transport the fluid with high slipstream velocity departing from the central wake region more efficiently, which explains why the slipstream velocities at the TSI monitoring points are significantly larger for the SG case. The difference of slipstream velocity between the two ground configurations becomes more significant with the bottom wall approached. Highlights: The effects of ground configurations on the slipstream and near wake of a HST are numerically investigated with IDDES. The SG case results in higher slipstream velocity relative to the MG case, especially near the ground. The longitudinal vortices, always corresponding to high slipstream velocity, oscillate more violently for the SG case. The fluid with high slipstream velocity is transported departing from the central wake more efficiently for the SG case.